Minimnya Kompetensi Seorang Guru Dalam Kegiatan Mengajar Di Kelas The Minimum Competence Of A Teacher In Class Teaching Activities - Gaby Agustina Nainggolan, Gelora Sembiring, Linton Naibaho, Putri Andini, Wulan Ayu Trisna, Yunita M (Pusdikra Publishing, 2023)
The teacher is the main facilitator at school, whose function is to explore, develop, optimize their potential so that they become part of a civilized society. The lack of professional teacher competence, the classroom atmosphere created by the teacher is less innovative and creative, as well as phenomena of lack of teacher competence such as still stuttering in mastering teaching material broadly and deeply so that it fails to present meaningful and useful learning activities for students. The purpose of this writing is How are the problems related to the lack of teacher competence. The method used is descriptive qualitative research with library research techniques. Research results Teachers must design teaching and learning interactions that are more dynamic to achieve the expected goals in the form of knowledge, skills, attitudes and social.